2018
DOI: 10.1021/acsami.8b06072
|View full text |Cite
|
Sign up to set email alerts
|

Frosted Slides Decorated with Silica Nanowires for Detecting Circulating Tumor Cells from Prostate Cancer Patients

Abstract: Developing low-cost and highly efficient nanobiochips are important for liquid biopsies, real-time monitoring, and precision medicine. By in situ growth of silica nanowires on a commercial frosted slide, we develop a biochip for effective circulating tumor cells (CTCs) detection after modifying epithelial cell adhesion molecule antibody (anti-EpCAM). The biochip shows the specificity and high capture efficiency of 85.4 ± 8.3% for prostate cancer cell line (PC-3). The microsized frosted slides and silica nanowi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
21
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 27 publications
(22 citation statements)
references
References 64 publications
(79 reference statements)
0
21
0
Order By: Relevance
“…Cells can be captured onto a nanostructured surface are then subsequently released for analysis. Antibody‐coated silicon nanowires, either grown stochastically on glass slides or patterned using nanosphere lithography, have been used to capture circulating‐tumor cells from blood samples. Porous silicon nanowires, grown inside microfluidic channels, have been used to capture an avian influenza virus (H5N2) with an efficiency of roughly 50% .…”
Section: Biochemical Sensingmentioning
confidence: 99%
See 2 more Smart Citations
“…Cells can be captured onto a nanostructured surface are then subsequently released for analysis. Antibody‐coated silicon nanowires, either grown stochastically on glass slides or patterned using nanosphere lithography, have been used to capture circulating‐tumor cells from blood samples. Porous silicon nanowires, grown inside microfluidic channels, have been used to capture an avian influenza virus (H5N2) with an efficiency of roughly 50% .…”
Section: Biochemical Sensingmentioning
confidence: 99%
“…At the cell membrane, they can modulate the ability of cells to form focal adhesions, complex multi‐protein assemblies that span the membrane and provide a physical anchor between the cell and the outer environment . This effect may be particularly pertinent on substrates with nanoscale features (geometry or porosity) that are on a similar length scale to filopodia (nanoscale, environment‐sensing cell protrusions) or integrin receptors (transmembrane proteins that facilitate external binding) …”
Section: Biomechanical Cuesmentioning
confidence: 99%
See 1 more Smart Citation
“…Si NWs prepared by chemical/ion etching [ 56 , 57 , 58 , 59 , 60 ] or their conjugates with thermo-responsive polymers [ 61 , 62 ] have found applications for the capture of tumour cells with extremely high yields (higher than 80%). Remarkably, Cui et al [ 56 ] demonstrated a wet-chemistry in-situ growth of silica NWs functionalized with epithelial cell adhesion antibody (anti-EpCAM) to bind circulating tumour cells, achieving a binding efficiency up to 85.4 ± 8.3% for prostate cancer cell line (PC-3). Importantly, such functionalized silica NWs enhanced the capture efficiency of PC-3 more than 70% with respect to the corresponding flat surface [ 63 ] ( Figure 3 a–c).…”
Section: Silicon-based 1d Nanomaterialsmentioning
confidence: 99%
“…Recent advances have demonstrated that the efficient capture of CTCs can be achieved using nanostructured biointerface materials designed with a synergistic combination principle of structure match and specic molecular recognition. [8][9][10][11] Among these, Hyeun et al found an effective approach (sensitivity: 73% AE 32.4 at 3-5 cells per mL of blood) to isolate and release CTCs from blood samples of pancreatic, breast and lung cancer patients, using functionalised graphene oxide nanosheets on a patterned gold surface. 12,13 On the basis of these advanced achievements, we investigate whether early stage screening of clinical PCa with PSA levels of 4-10 ng mL À1 can be assisted through the detection of CTCs to help us improve the diagnostic efficacy of PSA.…”
Section: Introductionmentioning
confidence: 99%